Intik̲h̲āb-i Muḥammad Qulī Qut̤b Shāh - Muhammad Quli Qutb Shah, Sultan of Golkunda, 1565-1612.; Ṣiddīqī, Muḥammad Akbaruddīn, 1913- (Naʼī Dihlī : Maktabah-yi Jāmiʻah, 1972)
Poems in old Urdu, with introduction and glossary.
In Urdu.
Mode of access: Internet.
Keywords: Poetry; Poetry; Poetry; Poetry